Assessment of the physical fitness of road cyclists in the step and ramp protocols of the incremental test - Michalik, K.; Danek, N.; Zaton, M. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The incremental test in laboratory conditions is a method commonly used to evaluate the maximal oxygen uptake and peak power output, which are the good predictors of cycling performance. But the best-designed protocol remains unknown. Therefore, the aim of this study was to examine the physiological and biochemical responses in the incremental ramp on cycle ergometer and to compare with the commonly used step in young road cyclists. METHODS: Fifty-seven road cyclists took part in the experiment. The tests included two visits to the laboratory during which the anthropometric measurements, incremental test on a cycle ergometer, and examination of acid-base balance and blood lactate concentration were made. A randomly selected half of the subjects made, as the first one, the STEP (50W·3min-1) Test and the RAMP Test (~0,27W/sec) a week later. The remaining cyclists made tests in the reverse order. RESULTS: The peak power output obtained in the RAMP was significantly higher than obtained in the STEP by 18.13W (P<0.05). The maximal oxygen uptake was higher by 1.5 (mL/kg·min) during the RAMP (P<0.05). The postexercise blood lactate concentration was significantly higher by 0.94 mmol/L (P<0.05) in STEP. CONCLUSIONS: We recommend the use of RAMP Test with linearly increasing workload to determine peak power output, maximal oxygen uptake and ventilatory threshold to precisely programming and control training of young road cyclists.